2006
DOI: 10.1080/10170660609509325
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Joint Maintenance and Stock Provisioning Policy for a Multi-Echelon Spare Part Logistics Network

Abstract: Spare part stock management attempts to ensure that the failed equipment items can be replaced immediately to maintain a sufficient productivity level. In maintenance, the inventory policy determination for spare parts is an important issue. The age-based preventive replacement policy may seek the least total cost for spare part replacement. Considering the criticality of equipment where it is installed, demand for a certain spare part can be categorized into critical and non-critical. The stock level for crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Non-identical Labor Simulation technique Optimization algorithm (Sarker and Haque 2000) No No Discrete event Design of experiment (Chen, Hsu, and Chen 2006) The aim of this paper is to explore specific gaps observed in the previous literature by optimizing preventive maintenance and spare provision policy under continuous review in a non-identical multicomponent manufacturing system through a combined discrete event and continuous simulation model coupled with an optimization engine. Three optimization algorithms are compared and examined, namely, Simulated Annealing, Random Solutions and Hill Climb.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Non-identical Labor Simulation technique Optimization algorithm (Sarker and Haque 2000) No No Discrete event Design of experiment (Chen, Hsu, and Chen 2006) The aim of this paper is to explore specific gaps observed in the previous literature by optimizing preventive maintenance and spare provision policy under continuous review in a non-identical multicomponent manufacturing system through a combined discrete event and continuous simulation model coupled with an optimization engine. Three optimization algorithms are compared and examined, namely, Simulated Annealing, Random Solutions and Hill Climb.…”
Section: Papermentioning
confidence: 99%
“…Discrete event simulation was expected to dominate as it is the most popular technique in modeling manufacturing systems (Jahangirian Alrabghi, Tiwari, and Alabdulkarim et al 2010). Studies either used a single optimization algorithm (Chen, Hsu, and Chen 2006;Ilgin and Tunali 2007) or conducted design of experiments (Sarker and Haque 2000;Boulet, Gharbi, and Kenn 2009). Table 1 also shows how the present study complements the previous research by the inclusion of labor, modeling through combined discrete event and continuous simulation and examining three optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The joint optimization models are developing with the change of maintenance policies from age-based, periodic/block to condition-based maintenance (CBM). The agebased policy has been applied in the joint optimization models, such as [4][5][6][7][8][9]. And the periodic/block policy is widely adopted in the joint optimization models; for example, Acharva et al [10] found a jointly optimal block preventive replacement and spare provisioning policy for a system consisting of several like units.…”
Section: Introductionmentioning
confidence: 99%
“…-To the best of our knowledge, Chen et al [147] are the only authors that consider a multi-echelon spare part network in a joint maintenance and inventory decision problem. This topic can be further investigated in future research.…”
Section: Future Research Directionsmentioning
confidence: 99%